2001
DOI: 10.1007/s11745-001-0689-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of n−3 fatty acids on coronary atherosclerosis: Results from SCIMO, an angiographic study, background and implications

Abstract: According to the model of "response to injury," the arterial endothelium is occasionally injured in hyperlipidemia, hypertension, diabetes mellitus and in other states known as risk factors. The ensuing inflammatory response is modulated by cytokines and growth factors, among them platelet-derived growth factor (PDGF), and monocyte chemoattractant protein-1 (MCP-1). In two independent studies, we demonstrated that mRNA levels for PDGF-A and -B and for MCP-1 are reduced after ingestion of n-3 fatty acids by hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…Existen numerosos estudios que avalan que el consumo de EPA y DHA ayudan en la prevención o tratamiento de una serie de patologías, sobre todo aquellas en las que la inflamación tiene un papel importante en su desarrollo (25,26,27,28).…”
Section: Importancia En La Salud Cardiovascularunclassified
See 1 more Smart Citation
“…Existen numerosos estudios que avalan que el consumo de EPA y DHA ayudan en la prevención o tratamiento de una serie de patologías, sobre todo aquellas en las que la inflamación tiene un papel importante en su desarrollo (25,26,27,28).…”
Section: Importancia En La Salud Cardiovascularunclassified
“…El estudio sobre "prevención de Aterosclerosis Coronaria Mediante Intervención con Ácidos Grasos Omega-3 de Origen Marino" demostró una reducción del desarrollo de la aterosclerosis al administrar dosis bajas de AGPI-3 1,65 g/día (76).…”
Section: áCidos Grasos Y Enfermedad Cardiovascularunclassified
“…Existen numerosos estudios que avalan que el consumo de EPA y DHA ayudan en la prevención o tratamiento de una serie de patologías, sobre todo aquellas en las que la inflamación tiene un papel importante en su desarrollo (31,32,33,34).…”
Section: Los áCidos Grasos Poliinsaturados Esencialesunclassified
“…The results showed that patients fed EPA ϩ GLA had a significant reduction in BALF ceruloplasmin (a measure of alveolar membrane permeability) Vol. 19,No. 6 both groups.…”
Section: Human Studiesmentioning
confidence: 99%
“…19,No. 6 son, provision of diets containing long-chain PUFAs, such as EPA and GLA, that are metabolized regardless of existing alterations in ⌬-6 desaturase activity may prove beneficial to critically ill patients with ongoing inflammatory processes.…”
mentioning
confidence: 99%